Højalter, liturgi og andagt: Betragtninger over Bernt Notkes alterskab i Århus Domkirke - Kaspersen, Søren (Hikuin, 1999)
High altar, liturgy and devotion. Reflections on Bernt Notkes altarpiece in Århus Cathedral. By Søren Kaspersen The altarpiece is a pentateuch with two stationary wings and a baldachin, a box-like predella with three partitions and two wings, an upper shrine also with two wings, and a crowning crucifix. It was donated to the church in 1479 by bishop Jens Iversen Lange who is represented both in sculpture on the top of the baldachine, together with an angel originally displaying his coat-of-arms, and in painting on the outside of the first pair of wings, related to St. Anne, the Virgin Mary and the Christ Child in prayer and meditation .Two aspects of the altar are treated: its main positions related to the liturgy and its devotional dimension related especially to its closed position. The discussion about the main positions of the altar is caused by a dominant conception in the literature of the last decades on the altarpiece, talking about a position for Advent(corpus closed but predella and upper shrine opened, cf. fig. 2), for Lent (corpus in middle position with the Passion cycle, predella and upper shrine closed, cf. fig. 3) and for the great feasts (corpus, predella and upper shrine opened, cf. fig. 5). In accordance with the few written sources, the article argues in favour of a closed position (corpus, predella and upper shrine closed, cf. fig. 1) for workdays, an open position (corpus, predella and upper shrine opened, cf. fig. 5) for the great feasts, and a total covering of the retable with clothes/curtains during Lent. Furthermore it suggests a middle position (corpus in middle position, predella and upper shrine (?) opened, cf. fig. 4) for Sundays: the Passion cycle concluding with the Resurrection is then illustrative of the weekly commemoration (Wednesday, Friday and Sunday) of the redemptive act of Christ, while the panels with the Mass of St. Gregory (fig. 10) and the ’Prayer for acceptance of the sacrifice’ (fig. 11) on the wings of the predella correspond with the Eucharist of the High Mass, which is also grounded in Christ’s sacrificial death and His resurrection. From this hypothesis it is most likely that the upper shrine was also opened on Sundays. The devotional aspect of the altarpiece is especially delineated by the Gethsemane scene on the predella (fig. 6), showing the three stages of Christ’s heartfelt and intense prayer before His sufferings, ’repeated’ in the prayer of bishop Jens Iversen Lange to the Virgin Mary (“mater dei sis se[mper] . .”), depicted just above (fig. 7a-b), and in his meditations on the three ’stages’ of the Incarnation. This representation with its window frames is interpreted as a meeting between the bride and bridegroom based upon the medieval understanding of the Song of Songs 2, 9 and as a metaphorical ’utterance’ on body and soul, on sight and hearing as the windows of the soul. Finally, the flower presented to the Child by Mary is connected with a certain genre of devotional books comparing the soul with a garden, as e.g. Kleine Middelnederlandse boomgaard-tractaat from the end of the 14th century and Thoofkijn van devotien (Garden of devotion) from 1487.